ASPEK-ASPEK PERKEMBANGAN REMAJA YANG DIPENGARUHI OLEH KELEKATAN ANTARA ORANG TUA DAN REMAJA - Agnes Agustina Sinta Dewi; Yustinus Windrawanto; Adhi Krisna Maria Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine aspects of adolescent development that are influenced by attachment between parents and children. The present study employs a qualitative research method, utilizing the systematic literature review approach. The data collection process involved utilizing the Google Scholar database to identify relevant literature sources. The inclusion criteria encompassed articles published between 2020 and 2025, written in the Indonesian language, in the form of primary articles, and containing the entire text. The selection process involved the application of inclusion and exclusion criteria derived from the PICOS framework, leading to the identification of ten articles that met the specified criteria. The study's results indicated the influence of parental and adolescent attachment on developmental aspects, including physical, emotional, cognitive, social, moral, and identity development. The study's findings underscore the pivotal role of communication and trust in fostering attachment between parents and adolescents.